IMPLEMENTATION OF THE ECONOMIC ORDER QUANTITY (EOQ) METHOD ON CV ANUGRAH SAKTI - Fania Inasari; Lardin Korawijayanti; Musyafa Al Farizi (Applied Accounting and Management Review (AAMAR), 2023)
The purpose of thi study is to determine the cost of raw material inventory which is more efficient by using the Economic Order Quantity (EOQ) method at CV Anugrah Sakti. Data collection methods in this study are interviews,observation, and documentation. This research uses comparative data analysis test to assess whether or not the efficiency of raw material inventory costs at CV Anugrah Sakti is significant. The results of this study indicate that the difference in inventory costs between the company's calculations with the Economic Order Quantity (EOQ) method for chicken feather raw materials is more efficient IDR. 189,043,691 and bread raw materials with EOQ are more efficient IDR. IDR1,457,285,871. With a frequency of ordering for chicken feather raw materials as much as 7 times, with orders made once every 41 days. While the raw material for bread waste is 3 times a year, once every 106 days.